Learning Science in Indonesian Curriculum from Time to Time - Zamista, Adelia Alfama (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
This article aims to analyze the science learning according to the curriculum in Indonesia. This is based on the dynamic development of the curriculum in Indonesia. The method used in this study is literature review with descriptive analysis techniques. There are two main analyzes carried out, namely: 1) knowing how science learning according to the curriculum from time to time and 2) knowing whether science learning applied to the Kurikulum Merdeka has been able to answer global challenges. The results of the study show that the Indonesian curriculum has experienced dynamic development, there have been 12 curriculum developments since Indonesia's independence until 2023. In terms of the implementation of science learning, science has become a compulsory subject since Indonesia's initial curriculum. As in the 1947 learning plan, there were already three subjects related to science, namely: natural sciences, earth sciences and life sciences. Furthermore, science learning is increasingly becoming the focus of education, for example in the 2013 curriculum which promotes a scientific approach.